Periodontal effects with self ligating appliances and laser biostimulation - Gianluigi Caccianiga; Giancarlo Cordasco; Alessandro Leonida; Paolo Zorzella; Nadia Squarzoni; Francesco Carinci; Claudia Crestale (Wolters Kluwer Medknow Publications, 2012)
Background: Recently, various biostimulation's effects of low energy laser irradiation have been reported. The present study was designed to examine the effects of low-energy laser irradiation on alveolar bone remodelling during orthodontic tooth movement and finally on formation of new keratinized gingiva. Materials and Methods: 22 patients and 27 teeth in vestibular mucosal without keratinized gingiva were selected. Every patient was treated with self ligating appliances. In every orthodontic session the patient was treated with Diode laser biostimulation. At the moment of debonding, 27 teeth involved in the research were evaluated in terms of quality and quantity of attached gingiva. BOP and CAL loss were investigated. Results: Every tooth considered at the end of orthodontic treatment showed an attached gingiva around the crown: The average of keratinized gingiva at the end of the study was 3.10 mm and the mean increasing at each month was 0,49 mm. Conclusions: The combination between self ligating appliances and laser's biostimulation could improve the differentiation of periodontal ligaments stem cells in fibroblasts, able to promote attached gingiva around the crown of the teeth erupted in oral vestibular mucosa.